Economic Benefits of a Traditional Market: Case of Ibarapa Central Local Government Area of Oyo State, Nigeria - Ben Olugbamila, Omotayo; Olufayo, Olushola; Caroline Ola-Omole, Motunrayo; Funmilayo Abiola-Falemu, Adekemi; Veronica Olusanya, Ronke (British Journal of Marketing Studies, 2024)
The study is centered on examining the economic advantages of traditional markets in Nigeria, specifically focusing on the Ibarapa Central Local Government Area of Oyo State. The research utilized a multi-stage sampling procedure, which involved the identification and selection of political wards, as well as the identification and selection of markets within these chosen political wards. From the initially identified ten political wards, five were purposely selected due to the presence of traditional markets. Within these wards, a systematic random sampling technique was employed to select one market out of every two identified. Additionally, streets and residential buildings were identified and selected for the administration of questionnaires. A total of 110 copies of questionnaires were administered to the residents. The findings of the study revealed that traditional markets contribute to economic benefits through various means, such as an increase in house rent and land value, job creation, social interaction, and information dissemination. However, the study also highlighted the gross inadequacy of market facilities, including toilets, pipe borne water, healthcare services, and security. In light of these findings, it is recommended that additional facilities, such as healthcare services, water closet toilets, pipe borne water, and security services, be provided. This will contribute to the improvement of the quality of services offered by traditional markets, ensuring their continuous economic benefits and the development of the study area.